A modernização tecnológica: seu patamar nos sistemas prediais hidráulicos e sanitários - Aro, Celso Ricardo (2004)
Our country current socioeconomic environment is critical, with significant reduction in the construction industry consumer trade and great competition among this sector corporations which, to keep producing, are obliged to rethink their way to do so. Then, since the 80´s, these corporations have been questioning their technological delay and the low quality of their products, investing, afterwards, in the sector modernization. In this context, this research proposes a discussion about the adopted actions for sector technological modernization in order to rationalize and improve quality, as well as its technological level, emphasizing the Pumbling Systems. To do so, bibliographies related to the subject have been consulted to get familiar to the problem and possible ways to face the question and, in a later moment, verify it using cases of study. A field research was held in medium and small construction corporations in Ribeirão Preto. It was structured with visits to the buildings, where items related to the problems were verified through a Check-list and, later, analyzed to determine the corporation technological level related to the Pumbling Systems. In this research, it was evidenced the construction corporation unconcern related to the Pumbling Systems and its less importance compared to another sub-systems, such as architecture and structures. The technological level found in these corporations brings out the evidence of management investment necessity, creation of standard procedures and evaluation and selection criterion of the work. Only after consolidating these questions, the introduction of technological innovations will achieve their purposes.